Effects of Dietary Supplementation with Lactobacillus reuteri Postbiotics on Growth Performance, Intestinal Flora Structure and Plasma Metabolome of Weaned Piglets - Dongfeng Sun; Wenfei Tong; Shaochen Han; Mengjun Wu; Peng Li; Youguo Li; Yunxiang Liang (Animals)
Probiotics and their postbiotics have the potential to improve the health and growth performance of piglets, which has brought them widespread attention in the post-antibiotic era. In the present study, the effects of dietary supplementation of Lactobacillus reuteri postbiotics on the growth performance, intestinal flora structure and plasma metabolome of weaned piglets were investigated. A total of 816 healthy male piglets with uniform weight were divided into two treatment groups: piglets in the control (CTR) group were fed with a basic diet, and the ones in the LAC group were fed with the basic diet supplemented with 500 mg/kg Lactobacillus reuteri postbiotics. There were six replicates in each group and 68 piglets in each replicate. The animal trial lasted for 30 days. The feces and blood of piglets were collected for investigation, and the growth performance during the trial was counted. Our outcomes show that dietary supplementation with Lactobacillus reuteri postbiotics had no effect on the growth performance of piglets; however, it reduced the mortality rate of piglets by 6.37%. The levels of total superoxide dismutase in the serum, propionic acid and butyric acid in the feces were elevated, and the content of malondialdehyde in the serum was decreased with Lactobacillus reuteri postbiotics-treated piglets (p < 0.05). The fecal flora sequencing results show that the relative abundance of Firmicutes and monoglobus was upregulated, and the relative abundance of Bacteroides was downregulated with Lactobacillus reuteri postbiotics-treated piglets (p < 0.05). In addition, the levels of propionic acid and butyric acid in the feces were positively correlated with the relative abundance of Firmicutes and negatively correlated with the relative abundance of Bacteroides (p < 0.05). The plasma metabolome results show that dietary supplementation with Lactobacillus reuteri postbiotics raised the level of coenzyme Q10 in the serum, and the abundance of coenzyme Q10 was positively correlated with the relative abundance of Firmicutes and the level of total superoxide dismutase in the serum. In conclusion, dietary supplementation with Lactobacillus reuteri postbiotics contributed to improving the antioxidant function and reducing the mortality of piglets by regulating the structure of intestinal flora and upregulating the content of coenzyme Q10 in serum.